Prevalence of Low HDL and High LDL Levels in Type II Diabetic Patients with Ischemic MCA Stroke - Virk, Muhammad Abdulrehman; Ahmad, Muhammad Uthman; Shahbaz, Ali; Mahmood, Hafiz Abad; Gul, Mehak; Shahnawaz, Iqra (Indus Journal of Bioscience Research, 2025)
Background: Type II diabetes mellitus is strongly associated with cerebrovascular disease, particularly ischemic stroke in the territory of the middle cerebral artery. Disorders of blood lipids are a frequent comorbidity in diabetic patients, with elevated low-density lipoprotein cholesterol and reduced high-density lipoprotein cholesterol playing central roles in endothelial damage, atherosclerosis, and plaque formation. Objective: To determine the frequency of high low density lipoproteins and low high density lipoproteins in stroke patients. Study Design: Descriptive cross-sectional study. Duration and Place of Study: This study was carried out from February to May 2025 in the Department of Medicine, Shaikh Zayed Federal Postgraduate Medical Institute, Lahore. Methodology: A total of 103 patients aged between 30 and 70 years with previously diagnosed type II diabetes mellitus and clinically suspected stroke were recruited through non-probability consecutive sampling. Diagnosis of ischemic stroke was confirmed on neuroimaging. Venous blood samples were obtained for assessment of lipid profile. Reduced high-density lipoprotein cholesterol was defined as values below 40 milligrams per deciliter in males and below 50 milligrams per deciliter in females. Elevated low-density lipoprotein cholesterol was defined as values above 130 milligrams per deciliter. Results: The mean age was 53.08±12.15 years, with males comprising 69.9% of participants. High LDL was observed in 59.2% of patients, while 29.1% demonstrated low HDL levels. No significant associations were found between lipid abnormalities and age, gender, BMI, hypertension, or family history of dyslipidemia. Conclusion: Elevated LDL and reduced HDL are common among type II diabetic patients with ischemic MCA stroke.